The language originality of Oleksa Syniavskyi in the history of the Kharkiv Philological School in the 1920s and 1930s - Черемська, Ольга Степанівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is devoted to the dynamic process of formation of the language consciousness of the prominent Ukrainian philologist, representative of the twentieth century Kharkiv Philological School. The features of the scholar’s language personality are characterized. The examples of the publicist and scientific texts of the philologist are analyzed and the language phenomena typical for different language styles and periods of activity of O. Syniavskyi as language personality are defined. The consideration of these language phenomena is topical in the context of modern problems of orthography norming the modern literary language.